Indonesian Soybean Import in International Trade - Sibuea, Faiz Ahmad; Sibuea, Mhd. Buhari; Safitri, Sri Ariani (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Indonesia's reliance on soybean imports due to inadequate domestic production, understanding the multifaceted influence of macroeconomic conditions on soybean imports, and analyzing the factors driving import decisions alongside the effectiveness of existing import policies in ensuring supply security and promoting domestic production. Data collection consists of secondary data obtained from several sources such as the Ministry of Trade (KEMENDAG), the World Bank and UN Comtrade. The data analysis method used are descriptive and panel data regression analysis with the Gravity model. The result of the level soybean import that the United States occupies the first position as the largest soybean exporting country to Indonesia. The share of US soybean exports is very large in Indonesia, reaching 72% of all soybean imports in Indonesia.The results of the panel data regression analysis show that the variable of import tariff, import price and import restriction dummy significantly affect with importing value of Indonesian soybean in the world trade. In addition, exchange rate and economic distance don’t significantly affect with importing value soybean. Implementing Indonesia's soybean policy is expected to help achieve soybean self-sufficiency and reduce dependence on soybean imports from soybean producing countries in the world. The Indonesian government has issued policies namely expanding land, providing superior seeds and technology. The domestic government needs to implement a protection policy by implementing an entry tariff policy. Keywords: soybean Indonesian, international trade, affecting imports, policy soybean, policy implementation